Biotransformation of eugenol by an endophytic fungus Daldinia sp. IIIMF4010 isolated from Rosmarinus officinalis. Issue 4 (16th February 2023) - Lone, Bashir Ahmad; Bhushan, Anil; Ganjoo, Ananta; Katoch, Meenu; Gairola, Sumeet; Gupta, Prasoon; Babu, Vikash
Abstract: Natural value-added compounds produced from biological sources have attained immense significance in medicinal, food, flavourings, and agrochemical industries. Further, biotransformation is a powerful tool used to produce value-added compounds cost-effectively and selectively. In the present study, biotransformation of eugenol using an endophytic fungus Daldinia sp. IIIMF4010 isolated from the fresh leaves of the plant Rosmarinus officinalis leads to the production of two known value-added compounds. The biotransformation reaction of eugenol (50 mM) resulted in the production of eugenol- β -D-glucopyranoside (6.2%) and vanillin (21.8%). These biotransformed products were further characterized by liquid chromatography-mass spectroscopy (LC-MS) and nuclear magnetic resonance (NMR). Graphical Abstract: UF0001